Comparison of Outcome of Unilateral Modified Bladder Neck Incision and Tamsulosin Therapy in the Treatment of Primary Bladder Neck Obstruction in Young Men - Islam, Mohammad Saiful; Gupta, Sudip Das (Sir Salimullah Medical College Journal, 2022)
Background: Primary bladder neck obstruction (PBNO) is a condition in which the bladder neck does not open appropriately or completely during voiding. Symptoms caused by primary bladder neck obstruction includes storage symptoms (Frequency, Urgency, Urge incontinence, nocturia) and voiding Symptoms (Poor urinary stream, hesitancy, incomplete emptying of bladder). Objective: To compare outcome of unilateral modified bladder neck incision with tamsulosin therapy in primary bladder neck obstruction in young men. Materials and Methods: This hospital based quasi-experimental study was conducted in the department of urology, Sir Salimullah Medical College Mitford Hospital. Patients with the diagnosis of primary bladder neck obstruction included in this study. Total 44 cases were included. Among them 18 were treated with unilateral modified BNI (Group A) and 26 were treated with tamsulosin therapy (Group B). Results: The mean age was found 31.11±4.77 years in group A and 34.15±5.42 years in group B. At 3rd and 6th month mean uroflowmetry (Qmax) was statistically significant (p<0.05) when compared between two groups. However, in group A and group B uroflowmetry (Qmax) was significantly increased when compared initial vs 3rd month and initial vs 6th month respectively. The study observed that after 3rd month following the treatment the retrograde ejaculation was not found in group A and 1(3.8%) found in group B. At 6th month retrograde ejaculation was not also found in group A and found 2(7.7%) in group B. At 3rd and 6th month retrograde ejaculation was not statistically significant (p>0.05). Conclusion: The outcome of unilateral modified BNI is better than tamsulosin therapy. All others adverse effect of both medical and surgical treatment was mild and transient that was acceptable in clinical practice. Sir Salimullah Med Coll J 2022; 30: 155-160